A cloud architecture for dynamic virtual organisations in transport logistics. (1st January 2013) - Karakostas, Bill
This paper proposes a cloud-based data sharing architecture for dynamic virtual organisations in the domain of transport logistics. Such VOs are described as dynamic because its members can join and leave on demand, reflecting the behaviour of physical transport chains. Members of the VO implement a community type cloud by sharing amongst them data resources over a cloud fabric. Data about the status and activities of the transportation chain are replicated intelligently across the participating nodes. The data cloud architecture proposed in this paper ensures that transport chain data are always available on demand to those that require them, while minimising unnecessary exposure of data and thus security risks. The approach is illustrated with a case study of a multimodal transport logistics chain VO.